2012
DOI: 10.1016/j.pain.2012.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical allodynia but not thermal hyperalgesia is impaired in mice deficient for ERK2 in the central nervous system

Abstract: Extracellular signal-regulated kinase (ERK) plays critical roles in pain plasticity. However, the specific contribution of ERK2 isoforms to pain plasticity is not necessarily elucidated. Here we investigate the function of ERK2 in mouse pain models. We used the Cre-loxP system to cause a conditional, region-specific, genetic deletion of Erk2. To induce recombination in the central nervous system, Erk2-floxed mice were crossed with nestin promoter-driven cre transgenic mice. In the spinal cord of resultant Erk2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 34 publications
6
34
0
Order By: Relevance
“…Throughout the experiment, we used a partial sciatic nerve ligation (PSNL) model as a neuropathic pain model (Seltzer model) as described previously [17]. Briefly, the sciatic nerve located in the right hind paw was exposed via a small incision and approximately 1/3–1/2 the diameter of the nerve was tightly ligated with an 8–0 silk suture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the experiment, we used a partial sciatic nerve ligation (PSNL) model as a neuropathic pain model (Seltzer model) as described previously [17]. Briefly, the sciatic nerve located in the right hind paw was exposed via a small incision and approximately 1/3–1/2 the diameter of the nerve was tightly ligated with an 8–0 silk suture.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify mechanical allodynia, paw withdrawal responses to mechanical stimulation were assessed with von Frey filaments as previously described [17]. Briefly, mice were habituated for at least 1 h prior to testing in a clear acrylic cylinder (20 cm in height and 10 cm in diameter) on an elevated mesh floor.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports show that thermal and mechanical hypersensitivities resulting from NGF differ from each other, both in time course - mechanical hypersensitivity lasting much longer (Mills et al, 2013) - and in central MAPKinase involvement (Ostubo et al, 2012) In an earlier paper we detailed the receptor and pathway intermediates involved in mechano-sensitization by NGF, when injected as in the present study (Khodorova et al, 2013). The initial steps in signaling for this sensory modality differ completely from those for thermal hyperalgesia, mechano-sensitization requiring neurotrophin binding to the p75 NTR and activation of nSMase, neither of which is involved in the thermal response.…”
Section: Discussionmentioning
confidence: 71%
“…The combined evidence suggests that PKMζ activity in both the periphery and the spinal cord contributes to thermal and mechanical hyperalgesia, although the pathways for activation may differ between these two modalities (Ostubo et al, 2012), and between peripheral and central loci (see Lewin et al, 1994). …”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that extracellular signal-regulated kinase (ERK) plays a decisive role in regulating inflammatory responses and neuropathic pain [22, 23]. A recent study also reported that ERK knockout mice exhibited decreased pain sensitization after formalin stimulation or partial sciatic nerve ligation [24]. Thus, inhibition of ERK activation may be a promising therapeutic target for the treatment of neuropathic pain [25–27].…”
Section: Introductionmentioning
confidence: 99%